2023
DOI: 10.14202/vetworld.2023.229-238
|View full text |Cite
|
Sign up to set email alerts
|

First seroprevalence and molecular identification report of Brucella canis among dogs in Greater Cairo region and Damietta Governorate of Egypt

Abstract: Background and Aim: Given the rise in stray and imported dogs in Egypt over the past 5 years, it is surprising that no report of Brucella canis infection in dogs or humans has been documented in Egypt's published papers. This study aimed to detect the presence of antibodies against the rough (B. canis) and smooth Brucellae among dogs in Egypt and to characterize the Brucella species circulating in dogs. Materials and Methods: Blood samples (n = 449) were collected from owned and stray dogs in the Greater Cair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Dogs in Colombia had a seroprevalence of 1.96% for B. canis [31]. In Egypt, research showed an apparent prevalence of 3.8% and an actual prevalence of 13.2%, with stray dogs having a higher estimated true prevalence of 15% compared to owned dogs at 12.5% [32]. Positive B. canis antibodies were also found in studies conducted in Italy, where 25 out of 2328 sera were positive (1.1%), and Brazil, where 72 out of 280 sera (25.7%) were positive results.…”
Section: Molecular Identificationmentioning
confidence: 99%
“…Dogs in Colombia had a seroprevalence of 1.96% for B. canis [31]. In Egypt, research showed an apparent prevalence of 3.8% and an actual prevalence of 13.2%, with stray dogs having a higher estimated true prevalence of 15% compared to owned dogs at 12.5% [32]. Positive B. canis antibodies were also found in studies conducted in Italy, where 25 out of 2328 sera were positive (1.1%), and Brazil, where 72 out of 280 sera (25.7%) were positive results.…”
Section: Molecular Identificationmentioning
confidence: 99%
“…Twenty EDTA blood samples were collected aseptically from the jugular veins of positive camels in Oxoid signal blood culture bottles and sent to the lab in an ice box. 22 Culture systems were incubated anaerobically at 37 °C, and the cultures that showed growth within 3 days were incubated both aerobically and anaerobically and examined daily for a week by allowing the blood broth mixture to flow over. The loop of growth is streaked on Tryptic soy agar and Brucella agar and incubated for 3-14 days.…”
Section: Isolation Of Bacteriamentioning
confidence: 99%
“…In Egypt, B. melitensis is the most prevalent Brucella species in ruminants [3] followed by B. abortus and less frequently by B. suis biovar 1 and 2 [4,5]. Recently, B. canis DNA was detected in the blood of stray and owned dogs in Egypt [6].…”
Section: Introductionmentioning
confidence: 99%